PENGARUH TEMPERATUR TERHADAP TINGKAT SERAPAN AIR DALAM BAHAN POLY (2-VINYL PYRIDINE -CO-STYRENE) - Wiendartun, Mr; Rusnayati, Heni; Karim, Saeful (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2001)
Hydrophilic properties of organic polymer such as Poly (2-Vinylpyridine- Co-Styrene) have been found to have a correlation with other physical properties especially the electric resistivity. In this work, we have studied one of the physical properties of a polymer material, Poly (2-Vinylpyridine- Co-Styrene), that is the electric resistivity. It was studied on the basis of its relation with the concentration, temperature, humidity and the distance between their electrodes. The sample fabricated consists of two types of consentration: 0.03 gr/ml and 0.05 gr/ml with the distance between the two electrodes are 0.40 mm and 0.80 mm respectively. Towards these samples, we investigated the resistance coefficient for every 2% change in humidity for both drying and watering processes. From the experiment we obtain the following results: 1) There is hysteresis during the watering and drying processes indicating the continuity of resistance of this material, 2) Sample with smaller distance of electrodes performs better than that of the longer ones, 3) Sample fabricated from solution with higher concentration performs better than that of the lower ones, 4) Room temperature plays a significant role on the performance of the polymer material between the associated electrodes. These results could be used as a stepping-stone toward the more advance research leading the determination of film stability, resistancy upon temperature variation etc, so that this polymer material could be further developed into the humidity sensor device material.Key words: Hydrophilic, electric resistance, humidity sensor and polymer.